Porcine Organotypic Epicardial Slice Protocol: A Tool for the Study of Epicardium in Cardiovascular Research - Maselli, Davide; Matos, Rolando S.; Johnson, Robert D.; Martella, Davide; Caprettini, Valeria; Chiappini, Ciro; Camelliti, Patrizia; Campagnolo, Paola (Frontiers in Cardiovascular Medicine, 2022)
The epicardium has recently gained interest in the cardiovascular field due to its capacity to support heart regeneration after ischemic injury. Models to study the epicardium of large animals in vitro are limited and mainly based on epicardial cell isolation/differentiation from stem cells, followed by 2D cells culture. In this method paper, we describe the procedure to obtain and culture 3D organotypic heart slices presenting an intact epicardium, as a novel model to study the epicardial physiology and activation. Epicardial slices are obtained from porcine hearts using a high-precision vibratome and retain a healthy epicardial layer embedded in its native extracellular environment and connected with other cardiac cells (cardiomyocytes, fibroblasts, vascular cells etc). Epicardial slices can be cultured for 72 hours, providing an ideal model for studying the epicardium physiology or perform pharmacological interventions/gene therapy approaches. We also report on methods to assesses the viability and composition of the epicardial slices, and evaluate their architecture in 3D through tissue decolouration. Finally, we present a potential application for a nanomaterial-based gene transfer method for tracking of epicardial cells within the slice. Crucially, given the similarity in morphology and physiology of porcine heart with its human counterpart, our system provides a platform for translational research while providing a clinically relevant and ethical alternative to the use of small animals in this type of research.